Stabilization of peat using sugarcane bagasse ash (SCBA) and cement as a stabilizer - Bakhir, M A; Abu Talib, M K; Madun, A; Md Dan, M F; Pakir, F; Md Yusof, Z (2023)
One of the main land types in Malaysia is peat, which has relatively soft soil with a high organic content, poor shear strength, and high compressibility. Therefore, in its natural state, peat is deemed unsuitable for supporting a construction site. Cement is one of the techniques used to stabilize peat. However, because so much cement is used, this process is not environmentally beneficial. at this work, the stabilization of peat was achieved by using Sugarcane Bagasse Ash (SCBA) at a ratio of 5% to 20% in lieu of Ordinary Portland Cement (OPC). To determine the strength of the soil and the differences in microstructure between treated and untreated soil, laboratory experiments on the physical, chemical, and mechanical properties have been carried out. Through testing unconfined compressive strength (UCS), the optimal mix of replacement SCBA with OPC, consisting of 15 PCBA, demonstrated enhanced strength. The microstructure of a sample of 100 PC with 15 PCBA that is hollow is reduced and becomes denser as a result of the filler material SCBA's reaction, as shown by a scanning electron microscope (SEM). The test Energy Dispersive X-Ray (EDX) with the lowered of carbon and calcium rise value shows the pozzolanic reaction. It may, indirectly, strengthen peat following stabilization